Patient Satisfaction Surveys. Issue 1 (January 2015) - Halsey, Matthew F.; Albanese, Stephen A.; Thacker, Mihir
<x xml:space="preserve">Abstract</x> Background: Patient satisfaction surveys (PSS) were originally designed to identify areas in need of improvement in patient interactions for individuals, practices, and institutions. As a result of the Affordable Care Act, the Centers for Medicare and Medicaid Services incorporated PSS into a formula designed to determine the quality of medical care delivered to hospital inpatients; the resultant score and rank will determine subsequent hospital payments. This survey was developed to evaluate POSNA members' knowledge of and experience with PSS. Methods: The POSNA Practice Management Committee developed a 14-question survey that was sent to all active and candidate members (850). A total of 229 members responded; and results were tabulated by answer and simple percentages were calculated for each question. Comments were reviewed and grouped by similarity to identify frequency. Results: A total of 82% of respondents were aware of PSS with 67% stating they were utilized in their setting. Utilization of PSS rarely alters clinical decision making. However, PSS do affect decisions regarding the patient experience; and 45% of respondents believe that PSS have utility with respect to business decisions. Fifty-nine percent of respondents feel that scores can be predictably improved. Less than half the respondents stated that they had a good or excellent understanding of PSS and only 48% believe that PSS are a valid measure of health care quality. Conclusions: POSNA members' knowledge of and experience with PSS are not universal or uniform. Although most agree that patient satisfaction does not drive clinical decision making, it does appear to impact business and clinic-flow decisions with the idea that it can be predictably improved. Despite this, members' self-assessed that knowledge is average and it is not clear to the members that patient satisfaction reflects medical quality. On the basis of these findings and as the impacts of PSS become more prominent, efforts to educate the members of POSNA about PSS should be enhanced. Furthermore, research to identify and develop best practices that enhance patient satisfaction and well-being while minimizing costs should be supported. Level of Evidence: Level IV.